An image bank of the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A pictorial educational kit on development in the Sahel is currently being produced by the International Centre for Continuing Education and Development (CIEPAC) and the Lyon Institute of Social Studies (IESL) in France. This image bank of the...